Genetic Polymorphism Based on β-napthyl Acetate in Different Age Group of Gambusia Affinis in Bangladesh (Journal of Bangladesh Academy of Sciences, 2012)
Genetic polymorphism of esterase isozymes was examined in different developmental stages of Gambusia affinis after staining with ?-napthyl acetate as substrate by 7.5% polyacrylamide gel electrophoresis. Samples were just after birth, seven, 14 days old fry, 21, 28, 35, 42, 49 days old  male and female. Altogether three esterase bands named as Est-1, Est-2 and Est-3 were observed. Est-1 was absent in seven samples out of 13, Est-2 was absent only in just after birth, Est-3 was  absent in seven different samples out of 13 samples. This result indicates that Est-1 and Est-3 were  less active and Est-2 was very active at ? napthyl acetate. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10917 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 39-44, 2012